Do fund managers have expertise? : evidence from Singapore's fund management industry. - Low, Wee Jia. (2010)
Singapore’s asset management industry has been growing rapidly over the last 5 years. For a burgeoning financial centre, fund management expertise is vital for attracting investment inflows. In this project, we investigate if funds that predominantly invest in the Stock Exchange of Singapore possess stock picking skills that yield significant abnormal returns. We apply the bootstrapping method together with Carhart 4-factor model and measured the excess returns generated by funds that invested mainly in Singapore from 2003 to 2008. Our findings are similar to various studies on the US and UK funds’ performance which concluded that fund managers generally do not have significant stock picking expertise.